2022
DOI: 10.3892/etm.2022.11500
|View full text |Cite
|
Sign up to set email alerts
|

LTBP2 inhibits prostate cancer progression and metastasis via the PI3K/AKT signaling pathway

Abstract: Biochemical recurrence (BCR) is a cause of concern in advanced prostate cancer (PCa). Thus, novel diagnostic biomarkers are required to improve clinical care. However, research on PCa immunotherapy is also scarce. Hence, the present study aimed to explore promising BCR-related diagnostic biomarkers, and their expression pattern, prognostic value, immune response effects, biological functions, and possible molecular mechanisms were evaluated. GEO datasets (GSE46602, GSE70768, and GSE116918) were downloaded and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…MYADM is notably overexpressed in African American men who experience biochemical recurrence within 5 years 30 . Zhang et al suggest that LTBP2 is not only a promising diagnostic biomarker for biochemical recurrence of prostate cancer but also plays a significant role in regulating the immune microenvironment, affecting responses to immunotherapy, and inhibiting cancer cell proliferation and metastasis through the PI3K/AKT signaling pathway 31 . PAPSS2, a gene associated with androgen synthesis, is proposed by Ibeawuchi et al to influence the progression of prostate cancer, where its gene deletion is closely linked to an increased risk of postoperative PSA recurrence, positioning PAPSS2 as a potential predictive biomarker for PSA recurrence 32 .…”
Section: Discussionmentioning
confidence: 99%
“…MYADM is notably overexpressed in African American men who experience biochemical recurrence within 5 years 30 . Zhang et al suggest that LTBP2 is not only a promising diagnostic biomarker for biochemical recurrence of prostate cancer but also plays a significant role in regulating the immune microenvironment, affecting responses to immunotherapy, and inhibiting cancer cell proliferation and metastasis through the PI3K/AKT signaling pathway 31 . PAPSS2, a gene associated with androgen synthesis, is proposed by Ibeawuchi et al to influence the progression of prostate cancer, where its gene deletion is closely linked to an increased risk of postoperative PSA recurrence, positioning PAPSS2 as a potential predictive biomarker for PSA recurrence 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent year, algorithms have been developed to predict tumor purity using gene expression data based on the TCGA database. For example, (36,37), breast cancer (38,39), colorectal cancer (40)(41)(42) and hepatocellular carcinoma (43), which demonstrated that such big-data-based algorithms are effective, although its utility on immune and/or stromal scores in glioblastoma multiforme (GBM) has not been explored in detail.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%